Guru Agama Katolik dan Kepemimpinan yang Humanis - Sitepanus Zebua (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
This article aims to examine the concept of humanist leadership that is lived and carried out by Catholic Religious Teachers in the learning and coaching of students. The approach used in this study is qualitative with a literature study method, which is sourced from Catholic Church documents, the Bible, and scientific literature related to educational leadership and humanism. The results of the study show that the humanist leadership of Catholic Religious Teachers is rooted in the example of Jesus Christ as a Teacher and Shepherd who prioritizes love, respect for human dignity, dialogue, and service. This leadership is manifested through empathy, justice, moral exemplarity, and the ability to build relationships that foster trust and responsibility of students. Thus, Catholic Religious Teachers who live humanist leadership are able to create an educational climate that is inclusive, liberating, and oriented towards the development of human personal integrity. This article is expected to be a theoretical and practical contribution to the development of the leadership competencies of Catholic Religious Teachers in the world of education.